2016
DOI: 10.1016/j.str.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

A Phosphomimetic Mutation Stabilizes SOD1 and Rescues Cell Viability in the Context of an ALS-Associated Mutation

Abstract: SUMMARY The majority of amyotrophic lateral sclerosis (ALS)-related mutations in the enzyme Cu, Zn superoxide dismutase (SOD1), as well as a post-translational modification, glutathionylation, destabilize the protein and lead to a misfolded oligomer that is toxic to motor neurons. The biophysical role of another physiological SOD1 modification, T2-phosphorylation, has remained a mystery. Here, we find that a phosphomimetic mutation, T2D, thermodynamically stabilizes SOD1 even in the context of a strongly SOD1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 64 publications
1
29
0
Order By: Relevance
“…The detailed procedures for Eris calculation were described previously (37). For mutations requiring significant backbone adjustment (e.g., small to large residues, Gly-to-Pro mutations), the flexible backbone mode was adopted in Eris, followed by molecular dynamic simulations as described previously (8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed procedures for Eris calculation were described previously (37). For mutations requiring significant backbone adjustment (e.g., small to large residues, Gly-to-Pro mutations), the flexible backbone mode was adopted in Eris, followed by molecular dynamic simulations as described previously (8).…”
Section: Methodsmentioning
confidence: 99%
“…By perturbing (stabilizing or destabilizing) a series of sparsely populated conformational states along the SOD1 misfolding pathway, researchers have gained valuable insight into the nonnative SOD1 conformers and subsequent cytotoxicity. For instance, a phosphomimetic mutation results in increased thermodynamic stability of the SOD1 native dimer and positively impacts motor neuron survival in a model of ALS (8). In contrast, Proctor et al (9) identified trimer-stabilizing SOD1 mutants and demonstrated that the elevated population of SOD1 trimers promoted cell death.…”
mentioning
confidence: 99%
“…Ser59 and Ser98 are phosphorylated through a direct interaction with Dun1 in response to oxidative stress and this directs SOD1 to the nucleus where it acts as a transcription factor for genes involved in the oxidative stress response (Tsang et al, 2014). While production of phosphorylated SOD1 in amounts necessary for biophysical characterisation is challenging, Fay et al (2016) constructed and crystallised a SOD1 Thr2Asp phosphomimetic mutant. The wild-type SOD1 structure is maintained by the Thr2Asp substitution but strengthens the dimer interaction and slows dissociation rates even when the Ala4Val mutation was present along with glutathionylation at Cys111.…”
Section: Oxidationmentioning
confidence: 99%
“…Previous novel SOD1 mutants have been constructed by point mutation, including W32S/W32F (34,35), C111S(36), T2D (37), and E133Q (38), however, these studies did not use predictions of thermodynamic stability as a condition for their selection. Other studies have analyzed the force--induced mechanical unfolding of a de novo designed SOD1 construct .…”
Section: Discussionmentioning
confidence: 99%